Kepercayaan dalam Memediasi Keamanan dan Persepsi Resiko terhadap Minat Beli Konsumen - Mellania Ariya Nitta; Nuruni Ika Kusuma Wardhani (IPM2KPE, 2022)
This study aims to determine the effect of trust as a mediating variable between security and perceived risk on consumer buying interest, and to determine the effect between security, perceived risk, and trust on consumer buying interest in Lazada consumers in Surabaya. This research method is quantitative. The sample in this study was 90 respondents using a non-probability sampling technique and the analytical tool used was SmartPLS 3.0. The results showed, a) that the path coefficient value of the security variable on trust was 0.512 and the p-value was 0.001, so the results of the study were positive and significant; b) the value of the path coefficient of the risk perception variable on trust is -0.029 and the p-value is 0.748, so the results of the study are negative and not significant; c) the value of the path coefficient of the trust variable on buying interest is 0.270 and the p-value is 0.109, so the results of the study are positive and not significant; d) the value of the path coefficient of the security variable on buying interest is 0.457 and the p-value is 0.001, so the results of the study are positive and significant; e) the value of the path coefficient of the risk perception variable on purchase intention is -0.179 and the p-value is 0.010, so the results of this study are negative and significant. In conclusion, of the 7 existing hypotheses, only 3 hypotheses have an influence including security affecting trust, security influencing purchase intention, and perceived risk influencing buying interest. While the other 4 hypotheses have no effect, namely risk perception has no effect on trust, trust has no effect on purchase intention, trust does not mediate the relationship between security and purchase intention, and trust does not mediate the relationship between perceived risk and purchase intention. Keywords: Security, Trust, Purchase Intention, Perceived Risk